1989
DOI: 10.1128/mcb.9.9.3744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a region within the Na,K-ATPase alpha subunit that contributes to differential ouabain sensitivity.

Abstract: To analyze determinants within the Na,K-ATPase a subunit that contribute to differential ouabain sensitivity, we constructed and expressed a panel of chimeric cDNA molecules between ouabain-resistant and ouabain-sensitive a subunit cDNAs. When introduced into ouabain-sensitive monkey CV-1 cells, ouabainresistant rat al subunit cDNA and chimeras in which the 5' end of ouabain-sensitive human al or rat OL2 subunit cDNA was replaced by the 5' end of rat al subunit cDNA conferred resistance to 100 ,uM ouabain. Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The presence of these polar uncharged amino acids in the M1͞M2 loop thus explains the high affinity for ouabain in chimera HN34͞56. It has to be mentioned that although the first mutagenesis studies suggested a primary role of the M1-M2 hairpin in ouabain binding to Na ϩ ,K ϩ -ATPase (7,12,13,31), later studies indicated that other parts of the enzyme are also involved in the interaction with ouabain (9-11, 15, 18-20, 32, 33). It has been suggested that the overall conformation of the first extracellular loop may influence ouabain sensitivity indirectly by altering the stability or structure of the intermediate of the Na ϩ ,K ϩ -ATPase catalytic cycle that is competent to bind ouabain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these polar uncharged amino acids in the M1͞M2 loop thus explains the high affinity for ouabain in chimera HN34͞56. It has to be mentioned that although the first mutagenesis studies suggested a primary role of the M1-M2 hairpin in ouabain binding to Na ϩ ,K ϩ -ATPase (7,12,13,31), later studies indicated that other parts of the enzyme are also involved in the interaction with ouabain (9-11, 15, 18-20, 32, 33). It has been suggested that the overall conformation of the first extracellular loop may influence ouabain sensitivity indirectly by altering the stability or structure of the intermediate of the Na ϩ ,K ϩ -ATPase catalytic cycle that is competent to bind ouabain.…”
Section: Discussionmentioning
confidence: 99%
“…It is now generally accepted that amino acids present in the first extracellular loop of Na ϩ ,K ϩ -ATPase are involved in the binding of ouabain (7)(8)(9)(10)(11). The border residues of this loop, Arg113 and Asp124, are responsible for the ouabain-resistant character of the rat enzyme (12,13).…”
mentioning
confidence: 99%
“…To assess the level of ouabain resistance derived from (4). The EBOpLPP expression system thus allows rapid and efficient analysis of the ouabain sensitivity of Na,K-ATPase a-subunit cDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…The three rodent ax-subunit isoforms differ -1,000-fold with respect to ouabain sensitivity. Cell lines transfected with rat a2 or a3 cDNAs express a ouabain-sensitive Na,K-ATPase, whereas cell lines transfected with rat or mouse atl cDNAs express a ouabain-resistant Na,K-ATPase (4,5,11,15). However, the molecular basis for differential ouabain sensitivity among a-subunit isoforms has not yet been elucidated.…”
mentioning
confidence: 98%
See 1 more Smart Citation